Previous History of Teachers and Children - Ode Yahyu Herliany Yusuf; Elisna Elisna; Hisna Hisna; Melianti Melianti; Sukarni Sukarni (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The teacher-child relationship is the interaction between the teacher and the child that occurs in the school environment. The interaction between the teacher and the child is important because it can affect the achievement of the child's abilities in various aspects of development. The teacher-child relationship can be established through teacher interaction with children, including through providing information, advice, ways to solve a problem, and examples of good habits to children. The child-teacher relationship takes time to develop. First, the child and the teacher need to form a relationship. Once a relationship is formed, it must be maintained. The development of moral values as the basis for building children's character must pay attention to the nature of the child itself. It is easiest for children to learn something when they see and do it themselves. This is because children are still learning to use their sensory organs, rather than the feelings commonly used by adults.